Macronutrient Fertility on an Irrigated Corn/Soybean in Rotation - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2021)
Effects of nitrogen (N), phosphorus (P), and potassium (K) fertilization on a corn/soybean cropping sequence were evaluated from 2013 to 2020 (corn planted in odd years) from a study initiated in 1983. Corn yield was near optimum at 160 lb/a N. Phosphorus and K fertilization alone increased corn yield 31 and 7 bu/a, respectively; and soybean yields 22 and 1.7 bu/a, respectively. As N fertilization increased, the response to P increased corn yield from 13 to 40 bu/a. The best return on fertilizer investment was when the N and P needs were met for both crops.
Keywords: fertilizer; corn; soybean; long-term fertility